Analysis of Health Workers’ Preparedness Factors in Disaster Management at Disaster Prone Area Community Health Centers - Nur Laily; Anggun Wulandari; Fauzie Rahman; Endah Labati Silapurna; Diva Dhiya Ulhaq (Lambung Mangkurat, 2024)
Indonesia is one of the most disaster-prone countries in the world. Around 87% of Indonesia's territory is prone to natural disasters. Floods are the most common natural disasters that hit Indonesia. Throughout 2018-2020, South Kalimantan experienced 73 floods. This research aims to analyze the knowledge and attitudes of health workers in disaster management regarding flood disaster preparedness at the Mataraman Community Health Center, Banjar Regency. Quantitative research was conducted using an analytical observational research method with a cross-sectional design. The population in this study were health workers who worked at the Mataraman Community Health Center, Banjar Regency. This study used a sample of 33 people with purposive sampling technique. The instrument used was a questionnaire. Data analysis was carried out using the chi-square test with a confidence level of 95%. The results of statistical tests between the knowledge and attitudes of health workers in disaster management on disaster preparedness with p-values of 0.555 and 0.708. In conclusion, there is no relationship between the knowledge and attitudes of health workers in disaster management on flood disaster preparedness at the Mataraman Community Health Center.